DIGITALIZATION OF THE TSANAWIYAH MADRASAH EDUCATION PROCESS IN CIMACAN DISTRICT, CIANJUR REGENCY IN SUPPORTING SMART VILLAGES - Khaerudin, Muhammad; Ramdhani M, Asep; Prasetyo, Adityo Budi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The strong current of globalization has driven advances in technology, information and communication which then brought and forced changes in governance for various sectors, ranging from education, business to government. Communication technology is seen as capable of acting as an effective and efficient solution to a problem. One of the main phenomena of this technological advancement is the emergence of the Industrial Revolution 4.0. The Industrial Revolution 4.0 is marked by the widespread use of the internet, with sensors that are getting smaller, stronger and cheaper. School Digitization is an implementation of new learning, which is prepared to face the industrial revolution 4.0. The characteristics of the new learning are student-centered, use multimedia, prioritize collaborative work, exchange information, and encourage critical thinking and problem solving. Students do not only learn in conventional ways by listening to lectures from teachers and reading textbooks. However, they are challenged to collect relevant information, collaborate with friends, and solve problems from the problems they face and present them.